2020
DOI: 10.1007/s40123-020-00277-3
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter, Retrospective Study (RE-ENACT 2) on Razumab™ (World's First Biosimilar Ranibizumab) in Retinal Vein Occlusion

Abstract: Purpose The REal life assessmENt of safety And effeCTiveness of Razumab 2 (RE-ENACT 2) study evaluated the long-term effectiveness of biosimilar ranibizumab. We present the subgroup analysis of patients with retinal vein occlusion (RVO). Methods Data of patients who received pro re nata (PRN) biosimilar ranibizumab (November 2015 to December 2018, 17 centers) were analyzed. Endpoints were change from baseline in best corrected visual acuity (BCVA, Snellen’s/logMAR), cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…The findings of this study are consistent with the data reported by Sharma et al (RE-ENACT study), and Sameera et al [ 19 21 22 23 24 25 ] The RE-ENACT (REal life assessmENt of safety And effeCTiveness of Razumab®) study conducted by the developers of the biosimilar drug (Intas Pharmaceuticals Ltd.) found significant improvements in visual acuity, central macular thickness, intra- and subretinal fluid with the use of the drug inpatients ( n = 561) with wet AMD, DME, and RVO for a duration of 12 weeks. [ 21 22 23 ] The RE-ENACT 2 ( n = 341) study evaluated the same variables for a longer-term (48 weeks) in patients with wet AMD, DME, RVO, and additionally in patients with myopic CNVM.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The findings of this study are consistent with the data reported by Sharma et al (RE-ENACT study), and Sameera et al [ 19 21 22 23 24 25 ] The RE-ENACT (REal life assessmENt of safety And effeCTiveness of Razumab®) study conducted by the developers of the biosimilar drug (Intas Pharmaceuticals Ltd.) found significant improvements in visual acuity, central macular thickness, intra- and subretinal fluid with the use of the drug inpatients ( n = 561) with wet AMD, DME, and RVO for a duration of 12 weeks. [ 21 22 23 ] The RE-ENACT 2 ( n = 341) study evaluated the same variables for a longer-term (48 weeks) in patients with wet AMD, DME, RVO, and additionally in patients with myopic CNVM.…”
Section: Discussionsupporting
confidence: 93%
“…[ 21 22 23 ] The RE-ENACT 2 ( n = 341) study evaluated the same variables for a longer-term (48 weeks) in patients with wet AMD, DME, RVO, and additionally in patients with myopic CNVM. [ 24 25 26 ] In the RE-ENACT study, all patients received three biosimilar Ranibizumab injections, but the RE-ENACT 2 study evaluated the patients who had been given one to five biosimilar Ranibizumab injections. Our study evaluated patients who had received one to three injections and observed a higher mean % change in CDVA (27.7%) and CFT (29.5%) at 1 month compared to RE-ENACT study (pooled analysis) which showed a change of less than 5% at 1 month.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 3 ] Sharma et al have also reported the drug to be safe and effective (Re-ENACT and Re-ENACT 2 Study). [ 4 5 ] However, there are a limited number of studies involving use of biosimilar with small sample sizes. In contrast, innovator molecules have been subjected to rigorous scrutiny with a large number of multicentric randomized control trials and real-world studies to establish their safety and efficacy.…”
mentioning
confidence: 99%
“…[ 11 12 ] Subsequently, the RE-ENACT-2 trial in nAMD showed significant improvement in BCVA, central subfield thickness, intraretinal and subretinal fluid at 48 weeks, whereas the analogous RE-ENACT-2 trial in RVO also showed Razumab as an effective treatment option in RVO by significantly improving the BCVA and reducing the macular thickness at 48 weeks. [ 13 14 ] Biosimilars of bevacizumab (Zybev ® , Zydus Cadilla, Ahmedabad, India; Bevatas ® , Intas Pharmaceuticals, Ahmedabad, India) are less often used as off-label by retina specialists. Our survey aimed to assess physicians' views and usage patterns of these biosimilars.…”
Section: Discussionmentioning
confidence: 99%